The Effect of Teachers' Motivation and Communication Style on Increasing Students' Interest in Learning Mathematics - Yana, Nurfitri; Husnita, Husnita (Universitas Veteran Bangun Nusantara, 2023)
This research investigates the impact of teacher motivation and communication style on students' interest in learning Mathematics. The background of the study highlights the critical role of these factors in enhancing student engagement and academic performance. The aim is to analyze the specific effects of teacher motivation and communication style on the learning interests of students. Utilizing a quantitative research method, data were gathered from 91 students through a questionnaire based on a 5-point Likert scale. The analysis employed multiple linear regression tests to assess the relationships. The results indicated that both teacher motivation and communication style significantly influence students' interest in Mathematics, both individually and collectively. The conclusion drawn from the study suggests that teachers should consistently provide motivation and maintain an effective communication style in the classroom to foster higher student interest in learning. Specifically, demonstrating openness in communication can create a comfortable learning environment, thereby enhancing students' engagement and interest in Mathematics. This research contributes to the education field by providing empirical evidence on the importance of teacher-student interactions in promoting academic interest and performance.